STUDI KOMPARATIF KONDISI LINGKUNGAN RUMAH DAN PENGENDALIAN VEKTOR ANTARA PENDERITA DAN NON PENDERITA DBD (Studi Kasus di Wilayah Kerja Puskesmas Kedung I Kabupaten Jepara Tahun 2021) - Akhna Khananiya; Arum Siwiendrayanti (Jurnal Kesehatan Masyarakat, 2022)
In 2021, dengue cases in the working area of Kedung I Public Health Center, Jepara Regency, showed an increasing trend of cases. A total of 59 cases of DHF were reported throughout 2021. This figure has increased from the previous year, which was 34 cases. Poor of home environmental conditions and vector control are risk factors for the transmission of DHF. The purpose of this study was to determine differences in home environmental factors and vector control between patients and non-patients of DHF in the working area of Kedung I Public Health Center, Jepara Regency. This research uses quantitative with retrospective design, comparative study method. The samples were 59 samples of patient group with total sampling technique and 59 samples of non-patient group with purposive sampling technique. The instruments used are questionnaires and observation sheets. Data analysis used is mann whitney statistical test. The results showed that there were differences in the conditions of TPA (p=0,038), use of mosquito repellent (p=0,035) and physical/mechanical control (p=0,009) between patients and non-patients of DHF. While the variables of presence of used goods (p=0,064), presence of hanging clothes (p=0,433), biological control (p=0,151) and chemical control (p=0,524) did not show a significant difference. The suggestion of this research is that every house sets one jumantik, and so that people are more aware to increase awareness of dengue disease by always implementing 3M plus.